2020
DOI: 10.5194/wes-2020-80
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Field experiment for open-loop yaw-based wake steering at a commercial onshore wind farm in Italy

Abstract: Abstract. The concept of wake steering in wind farms for power maximization has gained significant popularity over the last decade. Recent field trials described in the literature demonstrate the real potential of wake steering on commercial wind farms, but also show that wake steering does not yet consistently lead to an increase in energy production for all inflow conditions. Moreover, a recent survey among experts shows that validation of the concept remains the largest barrier for adoption currently. In re… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 8 publications
1
31
0
Order By: Relevance
“…Further, using CFD simulations, Cossu (2021) demonstrates that re-optimizing the blade pitch angle of a yawed wind turbine in below-rated operation can both reduce the power loss from yaw misalignment and increase the power gain from wake steering at downstream turbines. Through a wake-steering field experiment, Doekemeijer et al (2021) observe asymmetry in the power loss as a function of yaw misalignment, similar to the findings of Howland et al (2020), while also noting a relatively flat peak of the power curve as a function of yaw offset followed by a sharp drop in power production for more extreme offsets.…”
Section: Impact Of Yaw Misalignment On Power Productionsupporting
confidence: 69%
See 1 more Smart Citation
“…Further, using CFD simulations, Cossu (2021) demonstrates that re-optimizing the blade pitch angle of a yawed wind turbine in below-rated operation can both reduce the power loss from yaw misalignment and increase the power gain from wake steering at downstream turbines. Through a wake-steering field experiment, Doekemeijer et al (2021) observe asymmetry in the power loss as a function of yaw misalignment, similar to the findings of Howland et al (2020), while also noting a relatively flat peak of the power curve as a function of yaw offset followed by a sharp drop in power production for more extreme offsets.…”
Section: Impact Of Yaw Misalignment On Power Productionsupporting
confidence: 69%
“…Large increases in power -as well as significant reductions in the variability of the power production -were achieved at low wind speeds because wake steering caused the waked turbines to shut down less frequently by maintaining wind speeds above the cut-in speed. Last, Doekemeijer et al (2021) described a wake-steering experiment at a wind plant in Italy in which two turbines were controlled to improve the net power production for either a row of three turbines or pairs of turbines spaced 5.2D to 6.5D apart, depending on the wind direction. Using both positive and negative yaw offsets, the authors observed increases in energy production of up to 35 % for the two-turbine scenario and 16 % for the row of three turbines while also acknowledging net losses in energy production for certain wind directions.…”
Section: Introductionmentioning
confidence: 99%
“…Details of cross‐stream components of wake velocity have been examined by Martínez‐Tossas et al, 11 in which a ‘curled‐wake’ model is formulated, and by Shapiro et al, 12 in which yawed turbines are viewed as lifting lines. In recent developments, several wind tunnel studies (for example, 13‐16 ), numerical simulations (for example, 17‐20 ), as well as field studies (for example, 21‐26 ) have examined wake steering for wind farms of single‐rotor wind turbines, in which improvements have been seen in terms of both power output and reliability.…”
Section: Introductionmentioning
confidence: 99%
“…The P p exponent depends on the time-varying inflow. Additional inaccuracies arise in the cosine model since the power production as a function of the yaw misalignment is not generally symmetric in non-uniform flow (Howland et al, 2020d;Doekemeijer et al, 2021). Numerical experiments in Part 1 (Howland et al, 2020c) demonstrated that underestimating P p leads to poor wake steering performance.…”
Section: Model-based Closed-loop Wake Steering Control Methodology Updatesmentioning
confidence: 99%